The Core of the Non-Universe in Jaina Cosmology as a Cube of Eight Space-Points - Jadhav, Dipak (History of Science in South Asia)

(untitled) (University of Alberta Library, 2023)
According to Jaina cosmology, the non-universe is a hollow sphere beyond and exists all round the universe, whose middle region is the horizontal universe resting on a circular disc. The Bhagavatī Sūtra and the Sthānāṅga Sūtra each mention that there is the core of the horizontal universe where a cube of eight space-points is and from those eight space-points ten directions originate. This paper presents a conjectural explanation for understanding that cube. The core of the non-universe is the core of a core-sphere when the core-sphere is formed using n core-circles such that they are stacked up and down in the same order from the nth core-circle to the first core-circle. The upper four points of the cube of eight points form the core of the horizontal universe and the cube of eight points is the core of the non-universe. The nth core-circle becomes the horizontal universe when n is innumerable and the nth core-sphere forms the non-universe when n approaches infinity. This paper also shows that the intermediate and cardinal directions are linear and planar respectively while the zenith and nadir ones are three-dimensional.